Capital-embodied Technologies in CGE Models - James Lennox; Ramiro Parrado (Fondazione Eni Enrico Mattei (FEEM), 2015)
Computable general equilibrium (CGE) models are widely used to analyse macroeconomic and sectoral effects of climate policies. Developing new and improving existing carbon-free energy technologies will be crucial to limit the long-term economic costs of mitigation policies. Such technologies are largely embodied in capital goods; yet conventionally structured CGE models cannot capture capital-embodiment of sector-specific technologies. In this paper, we clarify the conceptual nature of the capital embodiment problem in multisector CGE models. Aggregating productive sectors and investment goods eliminates channels whereby specific technological changes are embodied in specific capital stocks. Nevertheless, capital-embodiment of sector-specific Hicks-neutral technical changes can be directly represented as investment-specific technical change (ISTC)
Keywords: O33; O44; Q54; Q55; Q58; 330; Climate Change Mitigation; Capital-Embodiment; Technological Change; CGE Models